Assessment of Physical, Thermal and Spectral Properties of Consciousness Energy Treated Cholecalciferol - Kumar Trivedi Mahendra; Jana Snehasis (Journal of Advances in Nanotechnology, 2021)
Cholecalciferol (vitamin D3) is used nowadays in nutraceuticals regarding the prevention and treatment of vitamin D deficiency and associated diseases. This study was done to analyse the effect of the Trivedi Effect® - Energy of Consciousness Treatment on the physicochemical, thermal, and spectral properties of cholecalciferol using PSA, PXRD, DSC, TGA/DTG, FT-IR, and UV-Vis analysis. For this study, the cholecalciferol sample was divided into control/ untreated and Biofield Energy Treated vitamin D3. The treated vitamin D3 sample received Biofield Energy Treatment (the Trivedi Effect®) remotely for 3 minutes by Mr. Mahendra Kumar Trivedi, who was located in the USA, while the test samples were located in the research laboratory in India. The treated sample was designated as the Biofield Energy Treated sample. The PSA analysis showed that the particle size values at d10, d50, d90, and D(4, 3) of the treated sample were significantly decreased by 5.80%, 16.49%, 17.52%, and 16.23%, respectively compared to the control sample. However, the specific surface area of the treated cholecalciferol was significantly increased by 7.26% compared to the control sample. Besides, the PXRD analysis revealed that the relative intensities regarding the characteristic diffraction peaks in the treated sample were significantly altered from -42.56% to 22.42%, along with -41.69% to 72.71% alterations in the crystallite sizes, compared with the control sample. Also, the treated sample showed 2.80% decrease in the average crystallite size. The DSC analysis showed a slight increase (0.24%) in the melting point of the treated sample along with 3.68% increase in the latent heat of fusion (ΔH) compared to the control sample. Also, the decomposition temperature of the treated sample was decreased by 0.29%, whereas the ΔH was increased by 5.79%, compared to the control sample. Moreover, the TGA/DTG analysis revealed the significant decrease in weight loss in the 1st and 3rd step of degradation of the treated sample by 18.58% and 89.81%, respectively, along with 1.83% increase in the maximum thermal degradation temperature compared with the control sample. Overall, the thermal stability of the treated cholecalciferol sample was observed to be increased in comparison to the control sample. Thus, the Trivedi Effect® might be used to produce a different polymorph of cholecalciferol, which possesses the improved qualities in terms of appearance, dissolution, absorption, bioavailability, and thermal stability as compared with the untreated sample. Thus, the Biofield Energy Treated cholecalciferol might be used in designing of better nutraceutical and pharmaceutical formulations possessing improved therapeutic response regarding the treatment of vitamin D deficiency associated diseases.
Keywords: Cholecalciferol